Comunicação rural em narrativas multimídia: uma proposta de divulgação do trabalho dos integrantes da Associação dos Produtores de Queijo Minas Artesanal do Cerrado - Caixeta, Laryssa Paiva (2020)
The work produced in rural areas supports the Brazilian economy and reaches the table of countless consumers. However, many times, the processes that involve the work of rural producers and their production remain in rural areas, causing little dissemination or appreciation of this work. This is what occurs in Minas Gerais in the milk production chain, with producers of Queijo Minas Artesanal (QMA) from do Cerrado. In view of this, the problem of this study was centered on: “How to disseminate the work of the members of the Associação dos Produtores de Queijo Minas Artesanal do Cerrado?”. To do so, it started from an exploratory methodological basis, which involved bibliographic, documentary and field research. From there, a proposal was developed to disseminate the work of these producers in digital media, through multimedia story, as a rural and institutional communication strategy. Thus, the intention was to publicize the Cerrado QMA - as a handmade, historical, traditional and cultural product - and the Associação dos Produtores de Queijo Minas Artesanal do Cerrado (APROCER), as a strong brand, capable of contributing to the strengthening of the Cerrado micro-region.